2014
DOI: 10.1051/0004-6361/201322721
|View full text |Cite
|
Sign up to set email alerts
|

A multi-method approach to radial-velocity measurement for single-object spectra

Abstract: Context. The derivation of radial velocities from large numbers of spectra that typically result from survey work, requires automation. However, except for the classical cases of slowly rotating late-type spectra, existing methods of measuring Doppler shifts require fine-tuning to avoid a loss of accuracy due to the idiosyncrasies of individual spectra. The radial velocity spectrometer (RVS) on the Gaia mission, which will start operating very soon, prompted a new attempt at creating a measurement pipeline to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…The calibrations are subsequently used to stack the noise-dominated transit spectra of faint objects and derive mission-average radial velocities through crosscorrelation techniques (Sect. 8.3;David et al 2014). For the brightest subset, epoch spectra and epoch radial velocities will be available.…”
Section: Cyclic Data Processingmentioning
confidence: 99%
“…The calibrations are subsequently used to stack the noise-dominated transit spectra of faint objects and derive mission-average radial velocities through crosscorrelation techniques (Sect. 8.3;David et al 2014). For the brightest subset, epoch spectra and epoch radial velocities will be available.…”
Section: Cyclic Data Processingmentioning
confidence: 99%
“…To meet the requirements of the FFT algorithm (see e.g. David et al 2014), the spectra were rebinned to a smaller, constant, log λ bin size and apodised at both edges by means of a cosine-bell function. David & Verschueren (1995) showed that the combination of an even and uneven number of points correctly chosen around the CCF summit allows reducing the impact of discretisation on the measurement of its location, hence on the RV determinations.…”
Section: Finding Reliable Orbital Elementsmentioning
confidence: 99%
“…The latter value being used to assess the bias significance using a two-tailed test (Eq. (20), David et al 2014). At the 1% significance level, it implies for what follows that an offset between two collections of measurements will be judged significant if the corresponding ∆RV/σ > 2.57.…”
Section: Comparison Between the Different Methodsmentioning
confidence: 99%
“…In this way, the median sky line shift obtained for the dataset is +0.19 km s −1 with a dispersion (measured as half the interquantile range from 15.87% to 84.13%, see Eq. (19) in David et al 2014) dispersion will be used throughout the text. The scatter reflects the mean precision and stability level of the wavelength calibration over the 3 years of observation.…”
Section: Spectroscopic Observationsmentioning
confidence: 99%
See 1 more Smart Citation